THE ADOPTION OF GENERATIVE AI AMONG INDONESIAN UNIVERSITY STUDENTS - Azrielira Callista Syavina; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The adoption of generative artificial intelligence (AI) tools has increasingly become part of Indonesian university students’ academic activities. This study explores the adoption of a generative AI tool among Indonesian university students. Using a quantitative survey approach, data were collected from 150 respondents through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine patterns in adoption behavior. The findings indicate that students’ adoption of generative AI is strongly connected to how they perceive its practical role in supporting academic work. Students who develop clear intentions to use generative AI tend to translate into adoption in their academic activities. Overall, this study highlights that the adoption of generative AI among Indonesian university students reflects a growing on AI tools as part of everyday learning activities.